DISCRIMINATION OF FEMALE DISCRIMINATION OF FEMALE DISCRIMINATION OF FEMALE A E D E S A E G Y P T I A E D E S A E G Y P T I A E D E S A E G Y P T I A E D E S A E G Y P T I (DIPTERA: CULICIDAE) (DIPTERA: CULICIDAE) (DIPTERA: CULICIDAE) (DIPTERA: CULICIDAE) FROM BANJARMASIN AND YOGYAKARTA BASED ON WING FROM BANJARMASIN AND YOGYAKARTA BASED ON WING FROM BANJARMASIN AND YOGYAKARTA BASED ON WING FROM BANJARMASIN AND YOGYAKARTA BASED ON WING MEASUREMENTS MEASUREMENTS MEASUREMENTS MEASUREMENTS - Abdul Gafur (Universitas Lambung Mangkurat, 2004)
Morphometric analysis of wing venation was performed for discrimination of females of three populations of A e d e s a e g y p ti previously could only be separated by gas chromatographic analysis of cuticular components. Images of detached wings observed under a microscope of low magnification were saved as bitmap files. Cartesian coordinates of termination and branching points of each wing were digitally recorded and were subsequently used in determination of interpoint distances. Two discriminant analyses using standardized distances selected 7 variables that could distinguish females of the three populations with 86.7% and 85% success rate. The differences in wing measurements gave further evidence of genetic separation of populations of the species.